Unethical Interactions between Physicians and Drug Companies - Singh, Harpreet (Gyan Management Journal, 2012)
Prescription drug industry usually employs unusual combination of marketing practices where the user (the patient) depends and relies upon the chooser (the physician) for selecting a drug therapy for him. Thus, the decision making for selecting drug therapy remains in the hands of the physicians. The medical profession is considered as one of the noble professions since the primary aim is to serve the humanity and provide a disease free society. In recent times lot of brainstorming is done around the world on the interactions between the physicians and the drug companies’ representatives. In this research paper an attempt has been made to review the prescription drug marketing system in India. An effort has been made to analyse the unethical pharmaceutical marketing activities responsible for influencing the physicians prescribing company promoted drugs.